Jocasta’s kinsfolk: Marx, Freud and Oedipus among contemporary antiphilosophers - Mikulić Borislav (Filozofija i Društvo, 2007)
The text deals with the recently renewed issue of ′antiphilosophy′ in the self-understanding of some prominent contemporary continental philosophers but not only them, such as Alain Badiou and Slavoj Žižek, both referring to the psychoanalyst and theoretician of discourse Jacques Lacan. Starting with a metaphorical analysis of the verdict made by Marx of ′merely interpretive′ character of philosophy in relation to ′the study of real world′ and with his comparison of philosophy with ′masturbation′, the text addresses new appeals to ′antiphilosophy′ as samples of a token or rather, as cases of a syndrome connected with Jocasta’s rationalization of Oedipus’ curse. It was her discourse based on general rules of rationality with which she unconsciously attempted to avoid the confrontation with the truth of an event (incestuous marriage) which had already occurred. In the text, presuppositions and consequences of such an analogy between ancient and contemporary philosophical material are discussed in order to show-on the basis of arguing that the unconscious is located within (and not beyond) rational processes that subjects undertake in order to respond to rational needs (viz. impulses of the Ego)-that contemporary discussion about ′antiphilosophy′ by left-wing philosophers bears unacknowledged tendencies to unconsciously reduce Marx’ algorithm of ′realization of philosophy′ to the Hegelian negation of the negation and to integrate it into the discourse of academic philosophy.